Intervenciones de enfermería y su influencia en la prevención de infecciones respiratoria aguda a preescolares del Centro de Salud La Unión de Babahoyo octubre 2018- marzo 2019 - Noboa Cedeño, Henry Joel (2019)
The project presented attempts to determine how nursing interventions influence respiratory infections in pre-school waters. Under the guidelines of the humanistic approach, considering that this holistic model indicates that nursing interventions focus on the care of one human towards another. The variables considered in the work were: nursing interventions (independent variable) and acute respiratory infections (dependent variables), in the study participated 51 mothers of preschool children attending the Babahoyo union health center, this project corresponds to an investigation multimetodo or mixed quantitative-qualitative research, exploratory-descriptive methodology, non-experimental research, transactional or transversal. Obtaining the informed consent of the mothers, the interview technique was used together with the survey instrument, together with the support of the theoretical exploration of representative authors and current research, the results showed us that the nursing interventions have a favorable influence on the measure is carried out in a pertinent-timely manner such as the PAE (assessment-observation, diagnosis, planning, execution and evaluation), otherwise it will be taken unfavorably, within the age range: children under 6 months and 2 years are respectively those who predominate this disease.